moi nguoi lam giup em may cau nay voi a

Question

moi nguoi lam giup em may cau nay voi a
moi-nguoi-lam-giup-em-may-cau-nay-voi-a

in progress 0
Dâu 1 year 2020-11-11T13:43:04+00:00 2 Answers 58 views 0

Answers ( )

    0
    2020-11-11T13:44:28+00:00

    a.

    `\sqrt{125} – 4\sqrt{45} + 3\sqrt{20} – \sqrt{80}`

    `=\sqrt{25*5} – 4\sqrt{9*5} + 3\sqrt{4*5} – \sqrt{16*5}`

    `=5\sqrt{5} – 4*3\sqrt{5} + 3*2\sqrt{5} – 4\sqrt{5}`

    `=5\sqrt{5} – 12\sqrt{5} + 6\sqrt{5} – 4\sqrt{5}`

    `=-5\sqrt{5}`

    b.

    `(\sqrt{99}-\sqrt{18}-\sqrt{11})\sqrt{11}+3\sqrt{22}`

    `=(\sqrt{9*11}-\sqrt{18}-\sqrt{11})\sqrt{11}+3\sqrt{22}`

    `=(3\sqrt{11}-\sqrt{11}-\sqrt{18})\sqrt{11}+3\sqrt{22}`

    `=(2\sqrt{11}-\sqrt{18})\sqrt{11}+3\sqrt{22}`

    `=2\sqrt{11}\sqrt{11}-\sqrt{18}\sqrt{11}+3\sqrt{22}`

    `=22-3\sqrt{22}+3\sqrt{22}`

    `=22`

    c.

    `2\sqrt{\frac{27}{4}}-\sqrt{\frac{48}{9}}-2/5\sqrt{\frac{75}{16}}`

    `=2/2\sqrt{27}-1/3\sqrt{48}-2/20\sqrt{75}`

    `=\sqrt{27}-1/3\sqrt{48}-1/10\sqrt{75}`

    `=3\sqrt{3}-1/3*4\sqrt{3}-1/10*5\sqrt{3}`

    `=3\sqrt{3}-4/3\sqrt{3}-1/2\sqrt{3}`

    `=7/6\sqrt{3}`

    d.

    `=3\sqrt{9/8}-\sqrt{49/2}+\sqrt{25/18}`

    `=3*3\sqrt{1/8}-7\sqrt{1/2}+5\sqrt{1/18}`

    `=9\sqrt{1/8}-7\sqrt{1/2}+5\sqrt{1/18}`

    `=9*1/2\sqrt{1/2}-7\sqrt{1/2}+5*1/3\sqrt{1/2}`

    `=9/2\sqrt{1/2}-7\sqrt{1/2}+5/3\sqrt{1/2}`

    `=-5/6\sqrt{1/2}`

    e.

    `(1+(5-\sqrt{5})/(1-\sqrt{5}))((5+\sqrt{5})/(1+\sqrt{5})+1)`

    `=(1+((5-\sqrt{5})(1+\sqrt{5}))/((1-\sqrt{5})(1+\sqrt{5})))(((1-\sqrt{5})(5+\sqrt{5}))/((1-\sqrt{5})(1+\sqrt{5}))+1)`

    `=(1+((5-\sqrt{5})(1+\sqrt{5}))/(1-(\sqrt{5})^2))(((1-\sqrt{5})(5+\sqrt{5}))/(1-(\sqrt{5})^2)+1)`

    `=(1+((5-\sqrt{5})(1+\sqrt{5}))/(1-5))(((1-\sqrt{5})(5+\sqrt{5}))/(1-5)+1)`

    `=(1+(5+5\sqrt{5}-\sqrt{5}-5)/(-4))((5-5\sqrt{5}+\sqrt{5}-5)/(-4)+1)`

    `=(1+(-4\sqrt{5})/(4))((-4\sqrt{5})/(-4)+1)`

    `=[1+(-\sqrt{5})](\sqrt{5}+1)`

    `=(1-\sqrt{5})(1+\sqrt{5})`

    `=1-(\sqrt{5})^2`

    `=1-5`

    `=-4`

    f.

    `1/(\sqrt{3}-\sqrt{2})+1/(\sqrt{3}+\sqrt{2})`

    `=(\sqrt{3}+\sqrt{2})/((\sqrt{3}-\sqrt{2})(\sqrt{3}+\sqrt{2}))+(\sqrt{3}-\sqrt{2})/((\sqrt{3}-\sqrt{2})(\sqrt{3}+\sqrt{2}))`

    `=(\sqrt{3}+\sqrt{2})/((\sqrt{3})^2-(\sqrt{2})^2)+(\sqrt{3}-\sqrt{2})/((\sqrt{3})^2-(\sqrt{2})^2)`

    `=(\sqrt{3}+\sqrt{2})/(3-2)+(\sqrt{3}-\sqrt{2})/(3-2)`

    `=\sqrt{3}+\sqrt{2}+\sqrt{3}-\sqrt{2}`

    `=2\sqrt{3}`

    0
    2020-11-11T13:44:51+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

    moi-nguoi-lam-giup-em-may-cau-nay-voi-a

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )